Learning Strategies Motivation Tadarus, Dzikir, And Prayer - Lubis, Mira Anggina; Lubis, Suci Asnia; Namini; Iswandi (Al Bahri: Journal of Islamic Education, 2024)
This article contains a discussion of learning strategies for enforcing rules through learning. Learning strategies are the steps taken by teachers to utilize existing resources to achieve learning goals effectively and efficiently. PAI learning strategies are traditional strategies, free strategies, reflective strategies and internal strategies. The method used in this journal is a qualitative descriptive method, with a library research approach. Based on the discussion in this journal, it can be concluded that the motivation learning model is through Tadarus, Dhikr and Prayer. A teacher must be a motivator or a good example for students to emulate. Motivation makes a huge contribution to education in worship, morals, arts and so on. And to implement these worship activities, a teacher can provide understanding or material so that students know how important it is to carry out worship activities. Apart from that, the teacher can also convey the benefits of these worship activities and the last thing is to practice these worship activities at school. In other words, in the exemplary learning process the factors that influence learning outcomes must be taken into account by the model. Because the best learning model is applied but without the attention, interest, motivation and activeness of students, the learning results obtained are not optimal. However, if the learning model is applied in learning and pays attention to the factors that influence learning outcomes, then learning outcomes will be maximized.